2022
DOI: 10.1371/journal.pdig.0000104
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and recommendations for wearable devices in digital health: Data quality, interoperability, health equity, fairness

Abstract: Wearable devices are increasingly present in the health context, as tools for biomedical research and clinical care. In this context, wearables are considered key tools for a more digital, personalised, preventive medicine. At the same time, wearables have also been associated with issues and risks, such as those connected to privacy and data sharing. Yet, discussions in the literature have mostly focused on either technical or ethical considerations, framing these as largely separate areas of discussion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…On the other hand, some challenges exist with other types of sensors used in remote patient monitoring systems. For instance, wearable devices, which often use a variety of sensors, have been associated with issues such as data quality, interoperability, health equity, and fairness [ 23 ]. Additionally, the reliability of data from some remote patient monitoring tools has been questioned, with error margins up to 25 percent reported for some popular fitness wearables [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some challenges exist with other types of sensors used in remote patient monitoring systems. For instance, wearable devices, which often use a variety of sensors, have been associated with issues such as data quality, interoperability, health equity, and fairness [ 23 ]. Additionally, the reliability of data from some remote patient monitoring tools has been questioned, with error margins up to 25 percent reported for some popular fitness wearables [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the ability of DL models to detect hyperkalemia, but they also found that as the number of input leads decreased, the overall performance deteriorated 14 . Furthermore, the efficacy of algorithms specifically designed for wearable devices like the Apple Watch, where the signal-to-noise ratio is typically lower, had not been extensively tested 30 . Nevertheless, we adopted several approaches to enhance single-lead Kardio-Net performance as cited in previous literature, including a moving window average prediction from 5-s ECG 31 , and noise detection and removal 32 .…”
Section: Deep Learning Models Have Previously Shown Proficiency In De...mentioning
confidence: 99%
“…Data bias and discrimination can occur if datasets are not representative of diverse populations or if algorithms are trained on biased data, leading to disparities in healthcare outcomes and exacerbating health inequities. To address these concerns, healthcare organizations must strive to collect inclusive and representative data, promote diversity in research and development efforts, and mitigate bias in data analysis and decision-making processes (Canali, et al, 2022;Rajkomar, et al ., 2018). In conclusion, ethical considerations are paramount in healthcare data solutions, encompassing privacy concerns, data security, and the fair and ethical use of data.…”
Section: Regulatory Framework Shaping Healthcare Data Solutionsmentioning
confidence: 99%